SOSIALISASI PENGGUNAAN KONSTRUKSI DINDING PENAHAN TANAH DI DAERAH SAWAH PASANG SURUT DESA BANYU URIP TANJUNG LAGO BANYUASIN - Mulyanda, Dhevi; Syahira, Nurul Aina; Sari, Siti Nur Indah; Syapitri, Nabilla Novia; Hania, Mariska Seli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
Banyu Urip Village, located in Tanjung Lago District, Banyuasin Regency, is one of the agricultural areas affected by tidal fluctuations. The unique hydrological conditions, influenced by the tides of the Musi and Banyuasin River Basins, cause high variations in groundwater levels and soil saturation. The dominant soil types in this area are soft clay and peat, which are classified as problematic soils due to their low bearing capacity and high compressibility. These characteristics often lead to damage to agricultural infrastructure such as irrigation channels, embankments, and retaining structures. This community service activity aimed to increase public understanding of appropriate retaining wall selection and construction methods for tidal rice field areas. The socialization involved educational sessions on soil characteristics, the function of retaining walls, and the use of locally available materials such as stone and gabions. The results showed an improvement in community knowledge and awareness regarding the importance of soil stability and the use of appropriate construction techniques to maintain agricultural productivity and infrastructure sustainability.